Personal Finances in the Era of Modern Technological Solutions - Warchlewska, Anna Janina; Janc, Alfred; Iwański, Rafał (Journal of Finance and Financial Law, 2021)
The purpose of the article: the aim of the article is to present the essence of personal finance management using modern financial technologies. The paper seeks to answer the question of the impact financial literacy and the growth of the fintech solutions have on personal financial management. Methodology: the analysis leads to an answer to the question of which determinants have an impact on consumers' financial decisions and what remote tools the market offers. The paper hypothesizes that the intensification of educational activities tailored to each age group by institutions offering financial services may influence the greater use of modern tools in the process of personal finance management. Theoretical considerations are based on an in-depth query of literature on the subject. Research and financial experimentation in the field of financial knowledge and skills are presented. The secondary empirical material is used to analyze the development of the FinTech industry. Results: The effectiveness of financial education is observed only in specific financial behaviors. The financial industry is shaped by recipients, who instead of financial education, look e.g. financial coaching for a specific problem at different stages of their lives. Changes in population structure (aging population) and a large group of customers from disadvantaged groups (e. i. seniors, disabled people) require the development of new, matched strategies by banks and financial services providers. Too much self-confidence and a low level of consumer knowledge of cybersecurity is becoming a challenge for modern financial technologies.